2021
DOI: 10.1108/bij-06-2020-0343
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risks associated with third-party logistics in restaurant supply chain

Abstract: PurposeThe restaurant network is reforming rapidly due to the advancements encountered so far in the restaurant–third party logistics (3PL) collaborations. These collaborations resulting from a strategical partnership between the restaurant and the 3PLs play a significant role in getting a good handle on the web, logistics activities, online business and many more services. Despite the collaborations, 3PL in the restaurant supply chain is associated with many risks that may hamper the supply chain's profitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Sensitivity analysis is a prominent analytic approach for determining how much the stability of a solution is affected by tiny changes in input values. (Mukhametzyanov and Pamucar 2018 ; Shanker et al 2021 ). Chang et al ( 2007 ) demonstrated how small differences in relative weights might lead to substantial differences in the final structure of components.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Sensitivity analysis is a prominent analytic approach for determining how much the stability of a solution is affected by tiny changes in input values. (Mukhametzyanov and Pamucar 2018 ; Shanker et al 2021 ). Chang et al ( 2007 ) demonstrated how small differences in relative weights might lead to substantial differences in the final structure of components.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Although this goes beyond the scope of this paper, COVID-19 and the measures associated with it such as lockdown and social distancing can have a detrimental impact on these businesses and their employees' wellbeing (e.g. Khan, 2020;Yang et al, 2021;Shanker et al, 2021;Tuzovic and Kabadayi, 2021).…”
Section: Ewl Related Factors: Size Sector and Ethnicity Contextmentioning
confidence: 99%
“…In order to combat variability and provide an answer to these questions, a sensitivity analysis was performed. Sensitivity analysis is a popular analytic technique utilised to determine how much a solution's stability depends on small input values variations (Shanker et al , 2021). A study by Chang et al (2007) demonstrated how minute variations in relative weights could result in large variations in the final structure of factors.…”
Section: Sensitivity Analysismentioning
confidence: 99%